Geometry, landmarks and the cerebral hemispheres: 2D spatial reorientation in split‐brain patients. Issue 2 (13th December 2016) - Prete, Giulia; Fabri, Mara; Foschi, Nicoletta; Tommasi, Luca
Abstract : A right‐hemispheric superiority in spatial encoding based on geometric cues has been largely documented in a variety of species, together with a left‐hemispheric specialization for encoding based on landmarks. In humans, hemispheric asymmetries for spatial encoding have been little explored. In this study, we compared a patient with a complete callosal resection (D.D.C.) and a patient with a wide callosal resection saving the splenium (A.P.), with healthy participants. In two 2D versions of the 'reorientation task', participants were asked to find the target corner of a rectangle‐shaped environment, by exploiting either geometric information alone or the combination of geometric and landmark information. In Experiment 1, the landmark consisted of a coloured side of the rectangle; in Experiment 2, this cue was replaced by a coloured disc located inside the rectangle. In both experiments, the rectangular shape ensured the geometric cue. D.D.C. was always unable to recall the target, whereas A.P. correctly solved the task when only the geometric information was available, without difference with respect to the controls. Importantly, the performance of A.P. did not differ from controls' when the right hemisphere was tested with the landmark cues (the task being carried out using the left hand), whereas when the left hemisphere was tested (right‐hand session) his performance was worse than controls' with the coloured side of the space, but it was better than controls' with the coloured disc. The results are discussed comparing them with data collected on other species, and with theories of spatial processing.